Silicon catalyzed C-O bond ring closing metathesis of polyethers - Ansmann, Nils; Thorwart, Thaddäus; Greb, Lutz (Angewandte Chemie. International edition, 2022)
The Lewis superacid bis(perchlorocatecholato)silane catalyzes C−O bond metathesis of alkyl ethers with an efficiency outperforming all earlier reported systems. Chemoselective ring contractions of macrocyclic crown ethers enable substrate-specific transformations, and an unprecedented ring-closing metathesis of polyethylene glycols allows polymer-selective degradation. Quantum chemical computations scrutinize a high Lewis acidity paired with a simultaneous low propensity for polydentate substrate binding as critical for successful catalysis. Based on these mechanistic insights, a second-generation class of silicon Lewis superacid with enhanced efficacy is identified and demonstrated.